The Effect of Left Ventricular Assist Device Therapy in Patients with Heart Failure and Mixed Pulmonary Hypertension. Issue 2 (February 2017) - Lim, Hoong S.; Howell, Neil; Ranasinghe, Aaron
Background: Diastolic pressure gradient (DPG) of ≥7 mmHg has been proposed to distinguish mixed pulmonary hypertension from isolated post-capillary pulmonary hypertension in heart failure (HF). We evaluated the changes in pulmonary hemodynamics with left ventricular assist devices (LVADs) in patients with DPG of ≥7 or <7 mmHg, and effects on peak oxygen uptake (VO2 ) in patients with advanced HF. Methods: Pre- and post-LVAD implant pulmonary hemodynamics (including right atrial (RA) pressures, DPG, pulmonary vascular resistance (PVR), pulmonary capacitance (PCap) and cardiac output), echocardiography, cardiopulmonary exercise test were measured in 38 consecutive patients. Results: Ten of 38 patients had baseline DPG ≥7 mmHg. There were no significant difference in baseline characteristics, peak VO2 and ventilation slope, but PVR were higher, and PCap lower in patients with DPG ≥7 mmHg. Pulmonary artery pressures improved in all patients, but PVR and DPG remained higher and PCap lower in patients with baseline DPG ≥7 mmHg after a median follow-up of 181 (IQR 153–193) days. Peak VO2 increased and ventilation slope reduced post-LVAD, and these improvements were comparable between groups. Only RA pressure reduction and exercise increase in heart rate were significant predictors of peak VO2 increase on multivariate analysis. Conclusions: Baseline DPG of ≥7 mmHg compared to DPG <7 mmHg have persistently lower PCap and higher PVR post-LVAD, but the increase in peak VO2 was comparable despite these residual pulmonary vascular abnormalities. The improvement in peak VO2 was related to reduction in right atrial pressure and exercise increase in heart rate.